2022
DOI: 10.1145/3473037
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Forest Fire Detection Framework Using Heterogeneous Wireless Multimedia Sensor Networks

Abstract: With improvements in the area of Internet of Things (IoT), surveillance systems have recently become more accessible. At the same time, optimizing the energy requirements of smart sensors, especially for data transmission, has always been very important and the energy efficiency of IoT systems has been the subject of numerous studies. For environmental monitoring scenarios, it is possible to extract more accurate information using smart multimedia sensors. However, multimedia data transmission is an expensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…It is observed that power aware computing algorithms were used but energy consumption had increased [24]. A framework that utilized smart multimedia sensors to extract more accurate information while minimizing the transmission of visual data was discussed and the framework employed a hierarchical structure that combined multimedia sensors with scalar sensors [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that power aware computing algorithms were used but energy consumption had increased [24]. A framework that utilized smart multimedia sensors to extract more accurate information while minimizing the transmission of visual data was discussed and the framework employed a hierarchical structure that combined multimedia sensors with scalar sensors [25].…”
Section: Introductionmentioning
confidence: 99%
“…With the constant maturity in its technology, it has been applied in many fields, such as weather monitoring, disaster monitoring, power line inspection, and disaster rescue. In particular, it is easy to operate, highly mobile, low cost, easy to maintain, lightweight, small volume, and has real-time inspection capabilities, etc., in forest fire prevention and forest patrol, and other operations can also show its advantages [9][10][11][12]. Using the images taken by UAVs as data, combined with computer technology such as image processing to identify forest fires, has been one of the most commonly used tools in forest fire monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…In a sensor network, each sensor node can collect measurements, process the data, and exchange information with its neighboring nodes under a given communication topology, making the sensor network suitable to deal with systems or processes in large scales or spatially distributed [1], [2]. Some successful practical applications can be found in forest fire detection [3], air pollution surveillance [4], [5], and industrial valve monitoring [6], etc.…”
Section: Introductionmentioning
confidence: 99%